Popular justice : presidential prestige and executive success in the Supreme Court - Yates, Jeff, 1965- (SUNY series in the presidency., 2002)
"Popular Justice explores the interaction between the presidency and the United States Supreme Court in the modern era. It assesses the fortunes of chief executives before the Court and makes the provocative argument that success is impacted by the degree of public prestige a president experiences while in office. Three discrete situations are quantitatively examined: cases involving the president's formal constitutional and statutory powers, those involving federal administrative agencies, and those that decide substantive policy issues. Yates concludes that, while other factors do exert their own influence, presidential power with the Court does depend, to a surprising degree, on the executive's current political popularity."--Jacket